O aviso prévio e as polêmicas alterações introduzidas pela Lei n.º 12.506/2011 - Rodrigues, Leandro Moreira da Rocha (2012)
This work has the scope to present, in a clear and objectively perspective, the most important details regarding the prior notice and the modifications introduced by the Law 12.506/2011. It will be analyzed the constitutional issue of the proportionality of the prior notice set forth in the article 7, XXI, of the Brazilian Constitution, going from the infra-constitutional legislation through the publication of the Law 12.506/2011. After this preliminary analyze, it will be considered the modifications and issues deriving from the above mentioned Law, based on judgements and, mainly, on scholars’ point of views